Education as a Factor in the Human Capital Competitiveness – PISA Testing - Vejvodová, Kateřina; Filipová, Alena, 1965-; Mokrejšová, Veronika, 1985-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This master thesis explains the significance of human capital, and especially the significance of one of its components, education, to economic growth in an aera characterized by extensive knowledge-sharing, emerging technology solutions and a higher demand for high-skilled workers. Firstly, the role of human capital is illustrated with use of traditional models of economic growth, so called Solow and AK model. Secondly, the thesis presents various approaches to human capital measurement with focus on education assessment and the main characteristics of Programme for International Student Assessment (PISA). It is then further elaborated on how PISA results are reflected in the economic growth rates and the thesis follows on an extensive range of secondary resources to describe the issue. Thirdly, in-depth interviews are conducted with Czech educators to identify whether PISA can be a suitable instrument for measuring the quality of the Czech schooling system and the quality of future human capital. Advantages and disadvantages of the Czech schooling system are also evaluated and solutions enhancing quality of the systems are presented in the paper. With the help of educational experts, it has been discovered, that PISA testing is a suitable tool for measuring the quality of the Czech education system and also for assessment of future human resources’ capabilities.
Vedoucí práce: Alena Filipová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses